2022
DOI: 10.14202/vetworld.2022.789-796
|View full text |Cite
|
Sign up to set email alerts
|

Acute and sub-chronic oral toxicity study of purple sweet potato (Ipomoea batatas [L.] Lam) yogurt in mice (Mus musculus)

Abstract: Background and Aim: Food safety is an important aspect to be evaluated in preventing any potentially harmful side effects of food product such as yogurt. The purple sweet potato yogurt product was developed to combine the benefits of probiotic activities in yogurt and the bioactive effects of anthocyanin in purple sweet potato. This study was performed to investigate acute and sub-chronic oral toxicity of purple sweet potato yogurt (PSPY) in mice. Materials and Methods: Acute oral toxicity was evaluated by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Elevated serum creatinine is considered an indicator of renal toxicity [26]. Changes in liver and kidney weight (gain or loss) are important indicators of organ damage following exposure to toxic substances [27,28]. Additionally, splenomegaly, characterized by spleen enlargement, can arise due to hematologic abnormalities or infections [29].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum creatinine is considered an indicator of renal toxicity [26]. Changes in liver and kidney weight (gain or loss) are important indicators of organ damage following exposure to toxic substances [27,28]. Additionally, splenomegaly, characterized by spleen enlargement, can arise due to hematologic abnormalities or infections [29].…”
Section: Discussionmentioning
confidence: 99%
“…Any natural product containing bioactive molecules integrated into food is known as a functional food. In this context, one of the widely used functional food currently being studied is PSPL ( Khairani et al, 2022 ). PSPL, also known as Ipomoea batatas (L.) Lam.…”
Section: Introductionmentioning
confidence: 99%
“…(18) This research used purple sweet potato-based yogurt (PSPY) made from purple sweet potato puree mixed with low-fat milk and bacterial starter (Lactobacillus bulgaricus ATCC 11842, Lactobacillus acidophilus ATCC 4356, and Bifidobacterium longum), which reported to be safe to consume based on in vivo study. (19) Previous studies have shown that purple sweet potato can reduce carbohydrate content in yogurt and improve its sensory properties. (20) Nonetheless, the data in present-day about the potential protective effect of the product on anthropometry, lipid metabolism, oxidative stress, and pro-inflammatory markers is still inadequate.…”
Section: Introductionmentioning
confidence: 99%